Influence of the Radial Gap on the External Gear Pump Performance - Alexander Mitov; Nikolay Nikolov; Ivan Kralov (Applied Sciences)
The paper presents a numerical and experimental study of the radial gap influence on the external gear pump performance. The numerical study is performed with a two-dimensional (2D) computational fluid dynamics (CFD) model developed and advanced in previous authors’ works. The experimental study is carried out on a laboratory test bench. The presented numerical results are accurate in the entire operating range (500–3500 RPM) of the pump, which is confirmed by comparisons between the CFD results, experimental data, and manufacturer’s technical documentation. The comparative analysis shows that the differences obtained during the verifications are in the range of −6.44% to 2.48%. An original methodology has been developed that allows us to obtain the volumetric efficiency and overall efficiency characteristics as a function of the rotation frequency of the pump at different values of the radial gap, using the manufacturer’s data for the same characteristics at a nominal radial gap and the results of CFD simulations. The analysis of the numerical and experimental results shows that a gap size of 0.04 mm is close to the limit value for the investigated pump, if it is not operated at a rotational frequency above the nominal. The presented methodology can also be applied to other types of hydraulic displacement pumps in order to evaluate their performance in the wear process and to predict the maximum allowable value of a specific design parameter under different operating modes.